California Banking in the Nineteenth Century: The Art and Method of the Bank of A. Levy - Eugene White (Rutgers University, Department of Economics, 1999)
An 1890s loan book of the Bank A. Levy permits a detailed examination of the lending operations of a private bank in California during the National Banking Era (1864-1914). This period has been intensively analyzed at the macroeconomic level, but there are few microeconomic studies of banks. This unregulated bank was well integrated into national money markets and lent to a broad cross section of the community. Although the bank appeared to adhere to the real bills doctrine, it provided medium term uncollateralized financing to business. The bank priced risk carefully, offering rates equal to the lowest in the country to its best customers while charging extraordinarily high rates to borrowers deemed risky. In the absence of modern accounting, close scrutiny of borrowers' businesses and personal lives overcame the asymmetry of information between borrower and lender, enabling the bank to fulfill a special intermediary role.
Keywords: G2; N2; 330; banking; National Banking System; real bills